Current therapy of fibromyalgia syndrome - N.V. Chichasova; E.V. Igolkina (Современная ревматология, 2014)
The data on pathogenetically significant parameters that are involved in pain perception in fibromyalgia (FM) patients (increased sensitivity or density of dopamine receptors D2, enhanced pain signal due to the elevated substance P level or insufficient modification of the pain signal caused by low serotonin level; allodynia phenomenon; and the psychosomatic component) are reported. New classification criteria of FM and assessment of severity of the symptoms included in these criteria are presented. The changes that have taken place in therapy of FM pain over the past decade are demonstrated: less frequent use of peripheral analgesics, tricyclic antidepressants; more frequent use of serotonin reuptake inhibitors (duloxetine, milnacipran) and pregabalin. The effectiveness and fair pain tolerability of pregabalin are demonstrated. The effectiveness and tolerability of duloxetine, milnacipran, and pregabalin are compared using the data of 17 randomized controlled trials.